The The Role of Instagram Sosial Media in MSME Development Nazeera.id Bekasi: Peran Media Sosial Instagram dalam Pengembangan UMKM Nazeera.id Bekasi - najwa malikah; Sabrina; Wahyunengsih (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Micro, Small and Medium Enterprises (MSMEs) are small independent business activities, do not require large capital and are in great demand by small traders. The development of MSMEs can have a positive impact on regional development and Indonesia's economic growth, expand job opportunities, play a role in the judicial process, improve people's welfare, and encourage national stability. However, to achieve this goal, we must make our best efforts to win the increasing global competition. So that MSMEs can be competitive in this modern era, MSME entrepreneurs can use social media for business development so that they can follow and always keep up with the times. that must be borne, especially by micro-entrepreneurs. The research method used by the researcher is a qualitative method with a descriptive approach. The sample in this study is a micro-entrepreneur from Nazeera.id using social media and interviewing data collection technology. The results of this study indicate that Nazeera.id SMEs can achieve many benefits by adopting and utilizing social media, such as lower operating costs, easier market reach, and increased business. The development of small businesses can make them more competitive as evidenced by increased sales compared to businesses that do not use social media.